Effect of Muslin Bagging Technique on the Control of Greater Date Moth:ArenipseSebella(Hamps)Lepidoptera:Pyralidae and Lesser Date Moth Batrachedra amydraula (Meyr) Lepidoptera :Mumphidaon On Data palm of Missan - Salih Kazim (University of Thi-Qar Journal of Science, 2019)
This study was conducted to combat Arenipses Sebella and Batrachedra amydraula by coveringbunch palm. The experiment started in March 2009 and 2010 in the gardens of the Aldfas within theMissan province. The experiment was conducted by using five treatments. The first treatment Spray bunchpalm nets Pyrethrum and the spray rate of every two months and that in March and may and July andSeptember. the second treatment are spraying pesticide coverage with the lifting of the cover recurringbunch nets sprayed with Pyrethrum mints in march and then covered with bags muslin directly for a periodof 60 days and reiterated the steps the same transaction in June.the third treatment is to cover bunch bagsbeginning of march until the harvest of fruits and fourth treatment is spraying pesticide in question.covergeimmediately until the harvest of fruits either fifth treatment of control.Results showed that the lowest infestation and intensity percentage of the fruits by two lepidopteristinsects. Greater and lesser date moths were in the fourth treatment, then in the third one. On the other handinfestation and intensity percentage were not significantly different from control first and the secondtreatment .in addition the weights of fruit at harvest under the influence of those transaction, the resultshowed superiority treatment and then the fourth treatment, while the third .was the lower weight is thetreatment of the fifth and the first and second. Bags injury also prevented other fruit pests such as insectstores and birds